Perlindungan Hukum Pelaku Usaha Online dalam Transaksi Jual Beli Online melalui Sistem Cash On Delivery - Nabila Alifa Ch; Diah Aju Wisnuwardhani (University of Merdeka Malang, 2022)
Buying and selling is an activity based on an agreement with the deliveryof (leveraging) and paying the agreed nominal between those who bindthemselves to buying and selling activities. With the development of the CashOn Delivery transaction system, in this case the background of this research isas a solution to legal issues related to how legal protection and legal remediesare carried out by business actors Trading Through Electronic Systems (PMSE)from the consequences of consumer negligence in educating themselves asconsumers. properly. This study uses a juridical-normative research methodthat focuses on formal norms (laws and regulations) in Indonesia. Thisstudy provides results that online business actors can still or can take legalefforts to protect their rights as business actors who carry out online buyingand selling transactions with consumers with the COD system with 2 legalremedies (Non-Litigation and Litigation). However, in dealing with legalissues in a civil manner, business actors can carry out non-litigation effortssuch as consultation, negotiation, conciliation, mediation which are easy, fastand economical.